Driving Innovation in Agriculture - Minton, Ernest J. (My University, 2024)
This informal report to the Kansas Legislature summarizes the wide-ranging impact of K-State Research and Extension in 2024, highlighting initiatives in agriculture, environmental stewardship, public health, and community development across Kansas.
RPT111_2024_01
Keywords: RPT111; Administrative and Research Reports; legislature